Opportunities for the development of pilgrimage tourism based on modern innovative forms - Uzakov Dzhamshid Norboevich (THE INNOVATION ECONOMY, 2026)
The article analyzes the possibilities of developing pilgrimage tourism based on modern innovative forms. It outlines ways to effectively promote religious-architectural monuments, historical sacred sites, and cultural heritage objects through the introduction of new technologies, digital platforms, and interactive services in the field of pilgrimage tourism. Based on international experience, the advantages of innovative solutions relying on smart technologies in service provision are revealed. In addition, proposals are developed for improving regional tourism infrastructure, enhancing marketing strategies, and creating comfortable conditions for pilgrims. The research results are aimed at increasing the economic efficiency of applying innovative approaches in the pilgrimage tourism sector, while highlighting the future development directions of this field both in the region and, in particular, in the context of Uzbekistan.